Tazkiyatun Nafs as a Foundation for Strengthening Character Education and Developing Akhlakul Karimah - Ilhaq Mumtaz; Hoerul Umam (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study investigates the effectiveness of the Tazkiyah-Integrated Character Education (TICE) model in enhancing the moral character of fifth-grade students at SDIT Asy-Syafi'iyah Garut. Amidst a moral crisis characterized by bullying, gadget addiction, and declining respect for parents, the research addresses the gaps in character education, particularly in Muslim-majority contexts. Utilizing a mixed-methods approach, the study employs a quasi-experimental design with 60 students, divided into an experimental group receiving the TICE intervention and a control group following conventional tahfiz learning. Quantitative results reveal a significant increase of 27.4% in the Akhlakul Karimah Assessment Scale (AKAS-24) scores for the experimental group, with a large effect size (Cohen's d = 0.82). Qualitative findings from participatory observations, teacher interviews, and student reflections indicate positive behavioral changes in discipline, empathy, and spiritual awareness. The integration of quantitative and qualitative data supports the modified theory of Spiritual-Cognitive Dissonance, highlighting the transformative potential of aligning spiritual values with daily behavior. The TICE model offers a systematic framework for character education, emphasizing the emotional, cognitive, and spiritual dimensions of student development. This research contributes to the literature on tazkiyatun nafs and provides practical recommendations for evidence-based curriculum development in integrated Islamic primary schools.